Interleukin-6 localisation in the synovial membrane in rheumatoid arthritis. - Field, M; Chu, C; Feldmann, M; Maini, R (Springer-Verlag, 1991)
Polyclonal antibodies were raised in rabbits against Interleukin-6 (IL-6) by immunisation with a synthetic peptide of identical sequence to the amino terminal 12 amino acids of human IL-6. These antibodies reacted with recombinant IL-6 by ELISA and stained the cytoplasm of the IL-6 secreting bladder tumour cell line T24. Staining was abolished by prior incubation of the antibody with the IL-6 peptide. F(ab')2 fragments made by pepsin digestion of the IgG were immunopurified, labelled with biotin and retained activity in the biochemical and histological assays. Sections of synovial membrane from patients with rheumatoid arthritis (RA) were stained with these antibodies, using an immunoperoxidase technique, and cells containing IL-6 were domonstrated in the thickened synovial lining layer and also in a perivascular distribution in the deeper synovium. In osteoarthritis there were fewer cells in the lining layer and hence localisation appeared similar in both the interstitial area and lining layer. Double-staining techniques with mouse monoclonal antibodies against cell subset markers in five RA synovial membranes showed that up to 13% of T-cells and 19% of antibody-producing cells stained for IL-6. However, up to 70% of the macrophages contained IL-6 and these were found in close proximity to Ig-producing plasma cells. This study showed that macrophages were the major cells of the immune system in which IL-6 could be localised in RA, and suggests a role for locally produced IL-6 in the stimulation of rheumatoid factor production.